2017
DOI: 10.1038/nri.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

How nutrition and the maternal microbiota shape the neonatal immune system

Abstract: The mucosal surfaces of mammals are densely colonized with microorganisms that are commonly referred to as the commensal microbiota. It is believed that the fetus in utero is sterile and that colonization with microorganisms starts only after birth. Nevertheless, the unborn fetus is exposed to a multitude of metabolites that originate from the commensal microbiota of the mother that reach systemic sites of the maternal body. The intestinal microbiota is strongly personalized and influenced by environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
230
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(234 citation statements)
references
References 79 publications
2
230
1
1
Order By: Relevance
“…It is well accepted that factors from fetal or placental origin as well as maternal factors are likely to have a potential role in the regulation of inflammation, lesion, and apoptosis . Existing evidence supports the concept that P. gingivalis induces inflammation and leads to apoptosis in trophoblasts .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is well accepted that factors from fetal or placental origin as well as maternal factors are likely to have a potential role in the regulation of inflammation, lesion, and apoptosis . Existing evidence supports the concept that P. gingivalis induces inflammation and leads to apoptosis in trophoblasts .…”
Section: Discussionmentioning
confidence: 98%
“…Preterm low birth weight (LBW) in humans (birth weight <2500 g and <37 weeks of gestation) has been recognized as the leading cause of neonatal mortality and morbidity due to poor adaptability and resistance . Fetal development has been shown to exert a far‐reaching and long‐lasting effect on the long‐term health of the offspring, and there are negative effects associated with the preterm birth (PTB) of neonates. Therefore, it is urgent that the numerous risk factors for PTB be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study demonstrated that exposure of germ-free mother mice to microbes during pregnancy shaped immunologic development and functions in the neonate, which was mediated by maternal microbe-derived molecules that transferred to offspring during pregnancy and breastfeeding (8). In addition, maternal indigenous gut microbes can be transferred to the unborn fetus in utero through the placenta during pregnancy and to the newborn through maternal milk during lactation, affecting offspring immune programming (9,10). Hence, understanding the compositional and metabolic dynamics of the maternal gut microbiome during pregnancy and lactation may provide insights into how the gut microbiota influences maternal and offspring health.…”
mentioning
confidence: 99%
“…Recent findings provide new mechanistic explanations for the wide ranging health protections of breastfeeding to both mother and infant. Human milk drives the development of a diverse gut microbiome and healthy gut epithelium, which underpin normal metabolic, immune, and neurological development 12. Recent work indicates that perturbations in gut immune “sensing” mechanisms after early cessation of breastfeeding may contribute to the risk of acute lymphoblastic leukaemia 13…”
mentioning
confidence: 99%